PENGARUH PENAMBAHAN LAURIL ALKOHOL TERHADAP SIFAT-SIFAT UJI TARIK KOMPOSIT KARET ALAM TERISI SILIKA - Rieska Wulandari Sianturi, Indra Surya (Universitas Sumatera Utara, 2018)
By using a semi-efficient vulcanisation system; the effects of lauryl alcohol (LA) as a new rubber additive on tensile properties of silica-filled natural rubber (NR) composites were investigated. The NR composites were filled by silica filler with a fixed loading, 30.0 phr (part per hundred rubber). The LA is a fatty alcohol based on palm kernel oil and incorporated into the silica-filled NR composites. The LA loadings were 1.0 phr, 2.0 phr, 3.0 phr and 4.0 phr. It was found that LA functioned as an internal plasticiser. As an internal plasticiser, LA decreased the tensile modulus and increased elongations at break of silica-filled NR composites. It was also found that LA increased the crosslink density and tensile strength up to 3.0 phr of LA loading. The 3.0 phr of LA was the optimum loading.